Nanoparticles Vaccines Now and Future! - Ayman AL-MARIRI (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
While the advanced use of effective vaccines has had an extraordinary impact on global health, there remain many diseases for which vaccines are not available. The concept of therapeutic infection vaccines is based on the activation of the immune system against infection after the presentation of microbes' antigens to provide long-term protection against an infection. Nanoparticles (The term "nanoparticle" refers to a crystallite or primary particle measuring less than 100 nm in size.) have shown great potential as delivery systems for infection vaccines as they potentiate the co-